Antimicrobial residues in milk and occurrence of clinical and subclinical mastitis in herds in the region of campinas, são paulo - Dos Santos A.F.S. (2014)
The aim of this study was to evaluate the occurrence of clinical and subclinical mastitis and antimicrobial residues in milk samples from mammary quarters of 259 lactating cows of five properties in the region of Campinas-SP, Brazil. The Tamis test and the California Mastitis Test (CMT) were used to diagnose clinical and subclinical mastitis, respectively. The somatic cells count (SCC) was done in milk samples of weigh jars and cooling tanks. The presence of antimicrobial residues was analyzed in milk samples of the mammary quarters, weigh jars and cooling tanks, with a microbiological test (Delvotest® SP). Milk samples were collected for microbiological isolation of mastitis-causing agents. Clinical and subclinical mastitis occurred in 2.32% to 16.66% and 21.00% to 69.1% of the mammary quarters, respectively. The SCC in the cooling tanks ranged between 221 and 1,124 x 103 cells/mL. Coagulase-negative Staphylococci were isolated in 45.93% of the milk samples. The analysis of the antimicrobial residues in the weigh jars and in mammary quarters showed 8.33% and 4.30% of samples testing positive, respectively. The presence of antimicrobial residues was detected in 5% of the cooling tanks. The findings point to the need to implement practices that focus on milk quality.